Evaluasi Kinerja Keuangan PT Campina Ice Cream Industry Tbk Dari Tahun 2018-2022 Menggunakan Pendekatan Common Size Pada Laporan Keuangan - Dwinanda, Salma Beinina; Sulistiyo, Hari (Peneliti.net, 2024)
Utilizing the common size methodology to gauge financial performance offers insights into an entity's achievements, elucidating how well the company's financial objectives have been met. This study endeavors to evaluate PT Campina Ice Cream Industry Tbk's financial trajectory from 2018 to 2022, employing the common size analytical approach. The research design adopted is descriptive, complemented by a quantitative methodology. Secondary data, specifically financial position statements and income statements, sourced from the company's publicly disseminated reports, serve as the foundational dataset. These data were subsequently scrutinized utilizing the common size analytical technique. Findings from the study reveal an upward trend in PT Campina Ice Cream Industry's financial performance between 2018 and 2022. Despite facing a downturn in 2020 attributable to the Covid-19 pandemic, the company managed to rebound and exhibited improved financial outcomes in both 2021 and 2022.